Intro to MSE - Physical Properties - Kitto, Kathleen (McGraw-Hill Education, 2018)
This DataVis project is part of a series of 10 projects designed for an Introduction to Materials Science and Engineering course. Students should download the project document below and then access the project in DataVis to complete the project. This project focuses on the Physical Properties for all Material Classifications.